THE INFLUENCE OF PATIENT SAFETY CULTURE MODEL TOWARD PRESSURE ULCER RISK PREVENTION IN A GOVERNMENT HOSPITAL IN BANJARMASIN - Jenny Saherna; Rina Annisa (CNJ: Caring Nursing Journal, 2018)
The basic purpose of bedrest for the patient supposed to the patient lies on the back in the bed for 24 hours to minimize all the patient’s organ system. The unsafety behavior, careless, lack of attention or motivation from the nurse to the patient can cause adverse event, such as pressure ulcer for the patient. Patient safety culture model for the nurse is better to decrease the number of accidents, the failed and also to optimally the service to the patient. The purpose of this study focused to examine the influence of patient safety culture model toward pressure ulcer risk prevention. This field research is mixed methods research model sequential explanatory. It used total sampling technique of 102 nurses in the five wards and quota sampling to select 3 informants from the patient culture control team in a Government Hospital. Multiple linear regression analyses were performed to identify qualitative data. Semi-structured guide in-depth interview used to collect the qualitative data. The summary of multiple linear regression analysis of all independent variables indicated that perceptions of patient safety were the most influential indicator to pressure ulcer risk prevention. The in-depth interview also indicated nurses’ perceptions of patient safety as an important factor that influences incident reporting, resources, and patient involvement as important factors that influence patient safety culture application on pressure ulcer risk prevention. Key Words : Patient Safety Culture Model, Pressure Ulcer Risk The basic purpose of bedrest for the patient supposed to the patient lies on the back in the bed for 24 hours to minimize all the patient’s organ system. The unsafety behavior, careless, lack of attention or motivation from the nurse to the patient can cause adverse event, such as pressure ulcer for the patient. Patient safety culture model for the nurse is better to decrease the number of accidents, the failed and also to optimally the service to the patient. The purpose of this study focused to examine the influence of patient safety culture model toward pressure ulcer risk prevention. This field research is mixed methods research model sequential explanatory. It used total sampling technique of 102 nurses in the five wards and quota sampling to select 3 informants from the patient culture control team in a Government Hospital. Multiple linear regression analyses were performed to identify qualitative data. Semi-structured guide in-depth interview used to collect the qualitative data. The summary of multiple linear regression analysis of all independent variables indicated that perceptions of patient safety were the most influential indicator to pressure ulcer risk prevention. The in-depth interview also indicated nurses’ perceptions of patient safety as an important factor that influences incident reporting, resources, and patient involvement as important factors that influence patient safety culture application on pressure ulcer risk prevention. Key Words : Patient Safety Culture Model, Pressure Ulcer Risk